Infant and maternal predictors of early life feeding decisions. The timing of solid food introduction. (1st September 2015) - Doub, Allison E.; Moding, Kameron J.; Stifter, Cynthia A.
Highlights: Feeding style predicts solid food introduction beyond demographic characteristics. Believing infants need solid foods <6 mo predicts earlier solid food introduction. Infant temperament may marginally influence the timing of solid food introduction. To promote guideline adherence, clinicians should address maternal feeding beliefs. Abstract: There is limited research on the maternal and infant characteristics associated with the timing of solid food introduction. The current study examined how maternal feeding style and infant temperament independently and interactively predicted the age at which infants were introduced to solid food. Data from 115 predominately white, middle-class mothers were collected when infants were 4 and 6 months of age. The timing of solid food introduction was positively correlated with mothers' age, education, breastfeeding at 4 months, self-reported responsiveness to infants' hunger and satiety cues, and negatively correlated with mothers' pre-pregnancy body mass index (BMI), beliefs about feeding infants solid food prior to 6 months of age, and infants' temperamental motor reactivity. When controlling for maternal age, education, pre-pregnancy BMI, and milk feeding method at 4 months, the timing of solid food introduction was negatively predicted by mothers' beliefs about feeding solid food prior to 6 months of age. Exploratory interaction analyses suggested that infant temperament marginally moderated maternal feeding style in predicting the timing of solid food introduction.